2014
DOI: 10.1093/gbe/evu001
|View full text |Cite
|
Sign up to set email alerts
|

The Plastid Genome of Mycoheterotrophic Monocot Petrosavia stellaris Exhibits Both Gene Losses and Multiple Rearrangements

Abstract: Plastid genomes of nonphotosynthetic plants represent a perfect model for studying evolution under relaxed selection pressure. However, the information on their sequences is still limited. We sequenced and assembled plastid genome of Petrosavia stellaris, a rare mycoheterotrophic monocot plant. After orchids, Petrosavia represents only the second family of nonphotosynthetic monocots to have its plastid genome examined. Several unusual features were found: retention of the ATP synthase genes and rbcL gene; exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 48 publications
2
92
0
1
Order By: Relevance
“…clandest i ne 68 . Previous studies have demonstrated that positions of IR junction and SSC region are correlated with degeneration of ndhF and ycf1 genes 57,69 . Loss of ycf1 and all ndh genes (including ndhF ), as revealed by this study may explain why SSC chloroplast genome regions of the two considered species are shorter than those of others.…”
Section: Discussionmentioning
confidence: 97%
“…clandest i ne 68 . Previous studies have demonstrated that positions of IR junction and SSC region are correlated with degeneration of ndhF and ycf1 genes 57,69 . Loss of ycf1 and all ndh genes (including ndhF ), as revealed by this study may explain why SSC chloroplast genome regions of the two considered species are shorter than those of others.…”
Section: Discussionmentioning
confidence: 97%
“…These organisms show extensive plastome reduction due to relaxed selective pressure on photosynthetic capacities because they are highly dependent on mycorrhizal fungi. Plastid genome rearrangements have been known to occur in heterotrophs, as observed in Petrosavia stellaris (Logacheva et al 2014); however, rearrangements were not observed in the sequenced section of C. dispar. The presence of rearrangements within the plastome remains tentative until it is completely sequenced.…”
Section: Plastid Reduction Within Mycoheterotrophsmentioning
confidence: 99%
“…2 0 1 3 ) and the mycoheterotrophic Petrosavia stellaris (Logacheva et al 2014). Previously, the only complete plastid genome data for mycoheterotrophic species were from the liverwort Aneura mirabilis (Wickett et al 2008) and three mycoheterotrophic orchids (Neottia nidus-avis, Logacheva et al 2011;Rhizanthella gardneri, Delannoy et al 2011; Corallorhiza striata var.…”
Section: Introductionmentioning
confidence: 99%
“…As we pointed out in a previous study (Logacheva et al, 2014), a quality of the plastome assembly from the low coverage genome sequence data depends on the relative coverage of plastid and mitochondrial genomes. The assembly was most successful for Leitneria, where we were able to completely reconstruct the plastome sequence (see below).…”
Section: Plastid Sequence Assembly and Annotationmentioning
confidence: 81%